Combined Intraarterial Carboplatin, Intraarterial Etoposide Phosphate, and IV Cytoxan Chemotherapy for Progressive Optic-Hypothalamic Gliomas in Young Children - Osztie, Eva; Várallyay, Péter; Doolittle, Nancy D.; Lacy, Cynthia; Jones, Gary; Nickolson, H. Stacy; Neuwelt, Edward A. (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Optic pathway and/or hypothalamic astrocytomas in children are often quiescent, but in some cases, more aggressive tumors may cause progressive visual, endocrine, and neurologic deterioration. The initial treatment of these gliomas includes surgery and IV chemotherapy. Radiotherapy is not recommended in young children because of its severe adverse effects on cognitive and neuroendocrine function. This report suggests a new approach using combined intraarterial and IV carboplatin-based chemotherapy for patients for whom first line treatment has already failed.METHODS: Six children (mean age, 57 months) with the diagnosis of optic pathway hypothalamic gliomas, who had tumor progression after surgery and underwent IV chemotherapy, were treated monthly with intraarterially administered carboplatin, intraarterially administered etoposide phosphate, and IV administered Cytoxan. Four of the children had histologically verified pilocytic astrocytomas, and in two cases, diagnosis was made on the basis of clinical findings. Administration of the intraarterial chemotherapy required catheter placement in both internal carotid arteries at the level of C2–C3 and into one of the vertebral arteries at the level of C6–C7, with the patient under general anesthesia.RESULTS: Four of six patients had partial radiographic response, one had stable disease, and one had progressive disease after one cycle. Three patients showed clinical improvement. There were no serious complications associated with the angiographic procedures. Toxicities included bronchospasm that resolved after 3 to 4 minutes in one patient. One patient showed mild ototoxicity, and four patients needed platelet transfusion because of hematologic toxicity of drugs.CONCLUSION: These results suggest that this modality of chemotherapy (administered after failure of systemic [ie, IV] chemotherapy), of progressive optic-hypothalamic astrocytomas in young children may be an effective treatment prior to radiotherapy.